Pengaruh Model Pembelajaran Aptitude-Treatment Interaction (ATI) terhadap Hasil Belajar Siswa Kelas IX MTs Patra Mandiri 1 Palembang pada Mata Pelajaran IPA Biologi - Abdurrahmansyah Abdurrahmansyah; Rian Oktiansyah; Eftalina Eftalina (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2017)
This study aims to determine the effect of application of learning models Aptitude -Treatment Interaction (ATI) on learning outcomes of students of class IX Mts Patra MandiriPalembang At IPA Subject Biology In this penelitiaan see if there are any learning effectAptitude - Treatment Interaction (ATI) sample in this study was a class IX student withstudent number 30.The method used is descriptive qualitative method. Data in the form ofstudent learning outcomes posttest score minus pretest score.The method used in this study isan experimental method , while the data collection techniques used are techniques andtests.The tests used to measure student learning outcomes,when the learning takes place.Theresults showed that students with different abilities, learning outcomes group 1 (high) , group2 (moderate), and group 3 (low) , obtaining learning outcomes did not differ (relativelysimilar). Activity level of students in the active category and responses given students topositive learning process it can be seen from the results of research that was successful tcount >ttable . Therefore it can be concluded that the cooperative learning model ATI can make studentlearning outcomes that have different abilities to be relatively the same which exceedMinimum completeness criteria and high category